Risk factors for Clostridium difficile infection in intestinal transplant recipients during the first year post‐transplant. Issue 2 (6th March 2018) - Guzman, L.; Qiu, F.; Kalil, A.C.; Mercer, D.F.; Langnas, A.; Florescu, D.F.
Abstract: Background: Clostridium difficile is the most common cause of healthcare‐associated infectious diarrhea. Risk factors for C. difficile infections (CDI) in intestinal transplant recipients (ITR) are not well‐defined. The aim of our study was to assess specific risk factors for CDI in ITR. Methods: This is a 1:3 case–control study that included 29 ITR who developed CDI (cases) and 87 ITR without CDI (controls) observed during the first year post‐transplantation. Wilcoxon rank sum and Fisher's exact tests were used to compare variables. Univariate and multivariable conditional logistic regressions analysis were performed to identify risk factors for CDI. Results: The multivariable conditional logistic regression analysis showed that proton pump inhibitors (PPI) administration (odds ratio [OR] = 0.06; 95% confidence interval [CI]: 0.007‐0.52; P  =   .01) was the only factor associated with lower rates of CDI. Outcomes for cases vs controls: rejection episodes 24.14% vs 20.69% ( P  =   .7), graft loss 0% vs 2.3% ( P  =   .99), and survival rate 1 year post‐transplantation 79.3% (59.6‐90.1%) vs 87.2% (78.1‐92.7%) ( P  =   .38). Conclusions: Proton pump inhibitor administration might be protective for CDI in ITR. Risks factors for CDI might be different in ITR compared to other populations; anatomical differences and medications administered in the post‐transplantation period may affect intestinal microbiota.